Safety of Concomitant Use of Corticosteroids and Traditional Korean Herbal Medicine for Facial Nerve Palsy: A Retrospective Study of Effects on Liver and Renal Function - Lee JY; Kim JH; Goo B; Nam SS (Journal of Multidisciplinary Healthcare)
Jee Young Lee,1 Jung-Hyun Kim,2 Bonhyuk Goo,2,* Sang-Soo Nam3,* 1Department of Korean Internal Medicine, Integrative Cancer Center, Cha Ilsan Medical Center, Goyang, Republic of Korea; 2Department of Acupuncture and Moxibustion, Kyung Hee University Hospital at Gangdong, Seoul, Republic of Korea; 3Department of Acupuncture and Moxibustion, Kyung Hee University College of Korean Medicine, Kyung Hee University Hospital at Gangdong, Seoul, Republic of Korea*These authors contributed equally to this workCorrespondence: Bonhyuk Goo, Department of Acupuncture and Moxibustion, Kyung Hee University Hospital at Gangdong, Seoul, Republic of Korea, Email goobh99@naver.com Sang-Soo Nam, Department of Acupuncture and Moxibustion, Kyung Hee University College of Korean Medicine, Kyung Hee University Hospital at Gangdong, Seoul, Republic of Korea, Email dangun66@gmail.comPurpose: Bell’s palsy is a peripheral neuropathy that requires early administration of high-dose corticosteroids as initial treatment. There is a lack of clinical evidence on the effects of herbal medicines on liver and renal function, as well as their interactions with conventional medicines. This study aimed to assess the safety of using herbal medicine and corticosteroids.Patients and Methods: To evaluate the effects of herbal medicine with corticosteroid liver and renal function, we analyzed the medical records of patients with facial nerve palsy. We defined drug-induced liver injury (DILI) according to Hy’s law and assessed causality using the Roussel Uclaf Causality Assessment Method. Kidney injury was defined by the Kidney Disease Improving Global Outcomes guidelines.Results: A total of 1076 patients were evaluated. Among 32 patients (3.0%) who showed abnormally increased liver function, 29 patients (2.7%) had possible DILI, and 3 patients (0.3%) had probable DILI, respectively, after concomitant use of steroids and herbal medicine. No case of drug-induced acute kidney injury occurred. There were no sequelae or irreversible damage to liver or renal function.Conclusion: The results of this study suggest that concomitant use of steroids and herbal medicine was safe for renal function but may be associated with hepatotoxicity in rare cases. Thus, proper monitoring is required when prescribing steroids and herbal medicines concurrently.Keywords: herbal medicine, corticosteroids, facial nerve palsy, liver function, renal function